2019
DOI: 10.5539/ies.v12n5p86
|View full text |Cite
|
Sign up to set email alerts
|

Co-Teaching in the “Academia Class”: Evaluation of Advantages and Frequency of Practices

Abstract: This article constitutes the continuation of a research process that investigated models and methods for co-teaching in the “Academia Class” program in the Ohalo Academic College (Nissim & Naifeld, 2018). The article focuses on the contribution of this program to all those who participated in it, identifying co-teaching practices and the connections between the sense of contribution and identification of those practices. The research relied on the collection and analysis of quantitative data. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
0
73
0
Order By: Relevance
“…Several studies show that this collaborative model has advantages over other training methods in terms of the prevention of student teacher dropout and the achievements of pupils during the first year of novice teachers' work. It was also found that the student teacher's sense of self-efficacy improved when they learned and taught pupils in schools as part of their teacher training according to the collegial model (Allen, Ambrosetti, & Turner, 2013;Hoy & Spero, 2005;Naifeld & Nissim, 2019;Latham & Vogt, 2007;Ridley, Hurwitz, Hackett, & Miller, 2005).…”
Section: Models Of Teaching Practicummentioning
confidence: 98%
“…Several studies show that this collaborative model has advantages over other training methods in terms of the prevention of student teacher dropout and the achievements of pupils during the first year of novice teachers' work. It was also found that the student teacher's sense of self-efficacy improved when they learned and taught pupils in schools as part of their teacher training according to the collegial model (Allen, Ambrosetti, & Turner, 2013;Hoy & Spero, 2005;Naifeld & Nissim, 2019;Latham & Vogt, 2007;Ridley, Hurwitz, Hackett, & Miller, 2005).…”
Section: Models Of Teaching Practicummentioning
confidence: 98%
“…It includes, on the one hand, a view of effectiveness by the teacher (e.g. Wilson and VanBerschot, 2014, Jurkowski and Müller, 2018, Neifeald and Nissim, 2019, Rabin, 2020 as well as a student view (e.g. Puttonen, 2014, Strogilos, King-Sears, 2019.…”
Section: Co-teaching Effectivenessmentioning
confidence: 99%
“…The view of effectiveness by teachers is usually the basis for revision of the methods used or modification of a new co-teaching course. Based on a pilot study, the teachers reflect the entire teaching process, finding the positives and negatives on which it is based when adjusting the course or educational activity to its final form (Kim et al, 2007, Wilson and VanBerschot, 2014, Neifeald and Nissim, 2019.…”
Section: Co-teaching Effectivenessmentioning
confidence: 99%
“…Co-teaching has been found to have several advantages in teacher training for both the trainer, the trainee and the pupils [17]. It was found that pupils receive many more learning opportunities and mediation, and their learning advances that their learning abilities are enhanced [18].…”
Section: Advantages Of Co-teaching In Teacher Trainingmentioning
confidence: 99%